Epidemiology of bovine trypanosomiasis in the Ghibe Valley, Ethiopia: Multiple-drug resistance and its effective control - Peregrine, A.S.; Mulatu, W.; Leak, S.G.A.; Rowlands, G.J. (1994)
In 1986 a project was set up to determine the constraints to production of Zebu cattle under trypanosomiasis risk in the Ghibe valley. Approximately 1800 East African Zebu cattle (EAZC) were resident within the Ghibe valleey during the experimental period (1986 - 1992) and were maintained under traditional management. Tsetse populations were surveyed using unbaited blue biconical traps from 1986 - to 1990, and traps baited with acetone and cow urine from 1990 - 1992, 600 eartagged EAZC from seven herds were monitored and weighed. These cattle were of varying ages. PCV below 26 percent were treated with diminazene aceturate as well as cattle with signs of trypanosomiasis. Three species of tsetse fly were detected; Glossina pallidipes, G. fuscipes and G. morsitans submorsitans. G.pallidipes was the predominant tsetse species detected. To determine blood samples were collected from parasitaemic cattle and then inoculated into calves. It is concluded that improved control of multiple-drug resistant trypanosome infections in cattle can be achieved if chemotherapy and tsetse control strategies are integrated.